Single phase grid connected power converter topologies with power pulsation compensation - Gottardo, Davide (2020)
Following the ever increasing penetration of grid connected distributed generation, EVs battery chargers, and distributed energy storage systems, the requirement for power converter having rated power ranging from 1 to 15kW is rising.